МАГНИТНЫЕ СВОЙСТВА ЛЕГИРОВАННОГО МАРГАНЦЕМ КРЕМНИЯ - Маджитов, М.Х. (Innovatsion texnologiyalar, 2022)
A large negative magnetoresistance phenomenon has been observed at room temperature by forming magnetic nanoclusters of manganese doped atoms in silicon by low-temperature diffusion. It has been shown that the negative magnetoresistance value can be controlled by controlling the concentration of manganese nanoclusters in silicon.